The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s40779-021-00344-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral microbiota in the oral-genitourinary axis: identifying periodontitis as a potential risk of genitourinary cancers

Abstract: Periodontitis has been proposed as a novel risk factor of genitourinary cancers: although periodontitis and genitourinary cancers are two totally distinct types of disorders, epidemiological and clinical studies, have established associations between them. Dysbiosis of oral microbiota has already been established as a major factor contributing to periodontitis. Recent emerging epidemiological evidence and the detection of oral microbiota in genitourinary organs indicate the presence of an oral-genitourinary ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 124 publications
0
22
0
Order By: Relevance
“…The global cardiovascular mortality report pointed out that many chronic infectious and inflammatory diseases, such as, interestingly, periodontitis, are associated with a significantly increased risk of cardiovascular adverse events (such as atrial fibrillation, myocardial infarction, and heart failure), ( Roth et al, 2015 ). Periodontitis shows a high expression of inflammatory mediators and markers, implying a high level of systemic inflammatory factors ( Pink et al, 2015 ; Sung et al, 2019 ; Fang et al, 2021a ; Yuan et al, 2021 ). A study involving 13,784 subjects, based on NHANES III, has shown that severe periodontitis is independently and significantly related to cardiovascular mortality in chronic kidney disease ( Sharma et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global cardiovascular mortality report pointed out that many chronic infectious and inflammatory diseases, such as, interestingly, periodontitis, are associated with a significantly increased risk of cardiovascular adverse events (such as atrial fibrillation, myocardial infarction, and heart failure), ( Roth et al, 2015 ). Periodontitis shows a high expression of inflammatory mediators and markers, implying a high level of systemic inflammatory factors ( Pink et al, 2015 ; Sung et al, 2019 ; Fang et al, 2021a ; Yuan et al, 2021 ). A study involving 13,784 subjects, based on NHANES III, has shown that severe periodontitis is independently and significantly related to cardiovascular mortality in chronic kidney disease ( Sharma et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms related to periodontitis and cardiovascular disease may be complicated ( Sanz et al, 2020b ). In general, the possible mechanisms involve the production and/or increased levels of inflammatory mediators caused by bacteremia, abnormal blood lipid metabolism, bacterial products and virulence factors, and bacterial colonization ( Miyakawa et al, 2004 ; Tonetti et al, 2007 ; Schenkein and Loos, 2013 ; Fang et al, 2021b ; Yuan et al, 2021 ). Our research directly confirms the association between heart failure and periodontitis, especially moderate/severe periodontitis, and provides clinical evidence for exploring specific mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Cavarretta et al [ 50 ] have also found that microbe could influence the tumor microenvironment of prostate cancer and promote tumor progression, another study suggests that bacterial metabolites (e.g. gingipains) may be involved in promoting the development of prostate cancer [ 51 ]. Other studies have found that microbe may affect the pathogenesis and progression of prostate cancer by regulating chronic inflammation, cytokines, apoptotic processes and hormonal production [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complicated interactions between tumors and inflammatory responses (20) have led to hematological inflammation-associated phenomena being used widely to predict the biological behavior of various tumors, including urothelial carcinoma. With regard to bladder cancer, studies have demonstrated the prognostic value of blood cell count, especially the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR).…”
Section: Discussionmentioning
confidence: 99%